PENINGKATAN BERPIKIR MATEMATIS DAN HASIL BELAJAR SISWA MELALUI PENDEKATAN PROBLEM BASED LEARNING PADA SISWA SMP - Finsensius Y Naja; Sofia Sa'o (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2023)
Formal education is one vehicle ‘for building quality human resources. The quality of human resources is very dependent on various aspects. One aspect that supports formal education is learning mathematics. This study aims to improve students' mathematical abilities and learning outcomes through a problem-based learning approach. This type of research is classroom action research with four stages, namely planning, implementation, observation, and reflection carried out in two cycles. Data was obtained from the instrument in the form of observations of mathematical thinking in the category of students' mathematical attitudes and tests to determine student learning outcomes. The subjects in this study were 20 class VII students of SMP Rewarangga Ende. The data analysis technique uses a comparative descriptive technique between cycles. The study results show an increase in students' mathematical thinking skills from the lowest initial level of 19% to 100% after the learning process in cycle II was carried out. At the same time, student learning outcomes have increased. This is known from the completeness of student learning outcomes, namely that from the initial test 20% increased in cycle II to 100%. Therefore, it can be concluded that Problem-Based learning can improve students' mathematical thinking and student learning outcomes in class VII students of SMP Rewarangga Ende.